Combating Corruption in Indonesia Through Islamic Criminal Law and Customary Criminal Law - Januaris, Fadli; Arwani, M. Khairul; Jumanda, Adi; Utama Yazid, Ilham; Ulfazah, Yernati; Fikri, Rahimatul (Yayasan Lembaga Studi Makwa, 2023)
Corruption is a big problem for the Indonesian nation that cannot be resolved temporarily. Now the practice of corruption occurs in almost all levels of society. Indonesia has become one of the leading countries in eradicating corruption. Even though the majority of Indonesia's population is Muslim. The purpose of this study is to formulate a definition of corruption in Indonesia from the perspective of Islamic law and how the concept of corruption works in Indonesia from the perspective of Islamic law. Use in this research descriptive-analytic method with a normative approach. The research results show that corruption in Indonesia is from the perspective of Islamic law an attempt to enrich oneself or others by violating the law contrary to the principles of justice (al-'is), accountability (al-amanah) and being in a position of responsibility. Corruption in Indonesia when viewed in terms of jinayat law in Islam is the same as the concept of Ghulul (fraud), and Risywah (bribery), and al-Ghasab (exploitation of other people's rights without permission). corruption so that it is included in the offense of Islam prohibiting corruption, then committing acts that are contrary to the texts, such as for example. However, the perpetrators are people who can be prosecuted according to law.